Leonard Becket, Stationer, and A help to discourse. (14th August 2018) - Cathcart, Charles
Abstract: This essay describes the publications of Leonard Becket, stationer and publisher, and presents a history of his publishing business. Becket built this business upon the success of the miscellany, A help to discourse; or, A miscellany of merriment . The article outlines the gradual development and expansion of A help to discourse through its many editions. This development appears in the light of Becket's eclectic and distinctive publications. The essay draws attention to the shared features of this corpus, notably the pervasive memento mori consciousness, the conduct book genre, the duodecimo form, the use of expansions as a marketing ploy, and the insistent tendency to appropriate contemporary verse for illustrative purposes. The essay first describes the various books that Becket sponsored and then offers a company history, one that explains how the enterprise felt its way towards the creation of its most valuable commodity and how it thereafter exploited its success.